Pharmacoeconomic Analysis of Drugs Used in the Treatment of Pneumonia in Paediatric Population in a Tertiary Care Hospital in India—A Cost-of-Illness Study - Lekha Saha (Medical Sciences, 2017)
Aims and objectives: The cost of antibiotic therapy for the treatment of pneumonia in the inpatient paediatric population can have a major impact on the healthcare expenditure. We planned to assess the direct and indirect costs of diagnosis and medical treatment of paediatric patients with community acquired pneumonia who are hospitalized in a tertiary care hospital in India. Methods: 125 children with a diagnosis of pneumonia who were admitted to the inpatient department of a paediatric hospital receiving antibiotic treatment were observed. Data on clinical presentation and resources consumed were collected and the costs of pneumonia treatment were calculated. Descriptive statistics (mean ± standard deviation (SD)) were used to evaluate data regarding demographics, drugs prescribed and cost (direct and indirect cost). Multivariate regression analysis was used to find out predictors of direct and indirect cost. Results: Among all pneumonia admissions, mild-to-moderate pneumonia constitutes 76.8%, and 23.2% children were admitted with severe pneumonia; 105 children out of 125 (84%) were suffering from associated disorders along with pneumonia. The majority of antibiotics prescribed belonged to beta lactams (52%) followed by aminoglycosides (19%), macrolides (13%) and peptides (11%). Parenteral routes of administration were used in a majority of patients as compared to oral. The average cost per patient in management of pneumonia was 12245 ± 593 INR ($187.34 ± 9.07).